2011
DOI: 10.1177/0954406211407799
|View full text |Cite
|
Sign up to set email alerts
|

The effects of radial inlet with splitters on the performance of variable inlet guide vanes in a centrifugal compressor stage

Abstract: Variable inlet guide vanes (VIGVs) can regulate pressure ratio and mass flow at constant rotational speed in centrifugal compressors as a result of inducing a controlled prewhirl in front of impellers. Radial inlets and VIGVs are typical upstream components in front of the first-stage impellers in many industrial centrifugal compressors. However, previous investigations on VIGVs in centrifugal compressors were mostly conducted under the condition of axial inlets, and this study aims to focus on the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Because of its high calculation efficiency, various operation conditions can be studied within limited time. Not only the energy performance of compressor and pump but also the detailed description of internal flow field can be obtained by means of commercial CFD codes, such as Numeca, 6 CFX, 8 Fluent, 30 and Tasc-flow. 31…”
Section: Experimental Measurement and Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its high calculation efficiency, various operation conditions can be studied within limited time. Not only the energy performance of compressor and pump but also the detailed description of internal flow field can be obtained by means of commercial CFD codes, such as Numeca, 6 CFX, 8 Fluent, 30 and Tasc-flow. 31…”
Section: Experimental Measurement and Numerical Simulationmentioning
confidence: 99%
“…Figure 1 shows a typical sketch of inlet guide vanes for a centrifugal pump, 5 and Figure 2 shows the pictures of inlet guide vanes equipment. 6,7
Figure 1.Centrifugal pump with inlet guide vanes (IGVs). 5
Figure 2.Geometry of variable IGVs.
…”
Section: Introductionmentioning
confidence: 99%
“…1 Many works have been carried out to investigate the influence of IGVs on energy performance, 2,3 internal flow field, 4,5 and unsteady interaction 6,7 for centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental and computational fluid dynamics (CFD) studies 4,6 showed that introducing preswirl increases the efficiency at lower mass flow rates and improves the surge limit. More recent studies have applied CFD simulations to investigate features such as performance, 7,8 unsteady interactions between the IGVs and the impellers, 9,10 pressure fluctuations at large IGV angles, 11 and the effect of IGV geometry. 1,12 A review of preswirl in from IGVs can be found in the work of Liu et al 13 Both experimental [14][15][16] and numerical 3,9,[17][18][19][20][21][22] approaches have been used to study compressor flow, with and without IGVs.…”
Section: Introductionmentioning
confidence: 99%